Analysis of Land Surface Temperature Distribution in Response to Land Use Land Cover Change in Agroforestry Dominated Area, Gedeo Zone, Southern Ethiopia - Wendwesen Taddesse Sahile; Gashaw Kibret Goshem; Seid Ali Shifaw; Muh. Rais Abidin (Three E Science Institute, 2023)
This study examined LST distribution in Ethiopia's agroforestry-dominated Gedeo Zone due to Land Use Land Cover change. For 2005, 2011, 2017, and 2022, 10 m Sentinel 2A and 30 m Landsat images were used to extract and map LST and LULC distribution. The DOS1 method corrected atmospheric errors in all satellite images. LULC change was detected using SVM image classification. The study result revealed that the Agroforestry and Built-up coverage has increased by 1520 sq. km and 2600 sq. km, respectively, from 2005 to 2022. The Bare Land and Farm Land coverage decreased by 1554 sq. km and 2565 sq. km, respectively, in the same period. The LST result has shown that there has been a remarkable variation in the spatial pattern of the LST between 2005 and 2022. The average LST in Agroforestry, Bare Land, Farm Land, and Built-up area has progressively increased over the years, from 19.6°C, 26.0°C, 20.2°C, and 25.58°C in 2005 to 25°C, 32.16°C, 28.23°C, and 30.62 °C in 2022, respectively. While in 2005, the maximum recorded LST did not exceed 37.3°C, by 2022, it had increased by close to 3°C, reaching 40.6°C. The overall result revealed that the average LST in °C has increased from 2005 to 2022. From the result, it was concluded that agroforestry had contributed a lot to LST distribution. LST may not depend on the local LULC change only; other factors like urbanization and global warming could play a significant role in changing LST locally and globally.